Voluntary conservation areas in Mexico: Scope and challenges - Peña-Azcona, Ivette (2022)
[Introduction]: In Mexico, the General Law of Ecological Balance and Environmental Protection (LGEEPA) includes instruments that promote social participation in land conservation, through voluntary mechanisms. Areas Voluntarily Destined for Conservation (AVDC) are a type of protected natural area under federal jurisdiction, which integrates a heterogeneous social participation. As of April 2022, there are 374 AVDCs in force, which maintain a total surface area of ​​606,132.11 certified hectares. [Objective]: This article analyzes the scope and challenges presented by the implementation of AVDCs, in an international context of voluntary land conservation strategies. [Methodology]: We applied an information triangulation process for a qualitative analysis, which included structured interviews, review of official files and bibliographic review. [Results]: Eight thematic categories of analysis were obtained: certification background, certified area, land tenure, certification terms, types of ecosystems, administration and operation, certification process, shared management, threats and strategies. [Conclusions]: There is a heterogeneity of experiences within the management of AVDCs that is determined by the types of land tenure, the local management capacities, the link with owner organizations, the types of governance and the interests that led to the establishment of the AVDCs. Ten key aspects of the current state of these reserves were identified, useful to understand the experiences of voluntary conservation that can contribute to direct evaluation processes of the effectiveness of their management.